Genetic landscape of congenital disorders in patients from Southeast Asia: results from sequencing using a gene panel for Mendelian phenotypes. Issue 1 (25th September 2020) - Wei, Heming; Lai, Angeline; Tan, Ee Shien; Koh, Mark Jean Aan; Ng, Ivy; Ting, Teck Wah; Thomas, Terrence; Cham, Breana; Lim, Jiin Ying; Kam, Sylvia; Goh, Chew Yin Jasmine; Lin, Grace; et al.
Abstract : Objective: To test the utility and diagnostic yield of a medical-exome gene panel for identifying pathogenic variants in Mendelian disorders. Methods: Next-generation sequencing was performed with the TruSight One gene panel (targeting 4813 genes) followed by MiSeq sequencing on 216 patients who presented with suspected genetic disorders as assessed by their attending physicians. Results: There were 56 pathogenic and 36 likely pathogenic variants across 57 genes identified in 87 patients. Causal mutations were more likely to be truncating and from patients with a prior clinical diagnosis. Another 18 promising variants need further evaluation for more evidence to meet the requirement for potential upgrade to pathogenic. Forty-five of the 92 clinically significant variants were novel. Conclusion: The 40.3% positive yield compares favourably with similar studies using either this panel or whole exome sequencing, demonstrating that large gene panels could be a good alternative to whole exome sequencing for quick genetic confirmation of Mendelian disorders. Abstract : The manuscript looks at Paediatric patients in Southeast Asia using next generation sequencing and confirms utility. The data describes next-generation sequencing results of 216 patients using the broad phenotype TruSight One Mendelian genes panel and identify causative mutations in 40.3% of patients, including 45 novel disease variants.